Follow‐up study of 2‐year‐olds born at very low gestational age in Estonia. (11th December 2012) - Toome, Liis; Varendi, Heili; Männamaa, Mairi; Vals, Mari‐Anne; Tänavsuu, Triinu; Kolk, Anneli
Abstract: Aim: To study very low gestational age (VLGA, <32 weeks) infants at 2 years of age and to identify the predictors of adverse outcomes. Methods: A population‐based cohort of 155 surviving VLGA infants born in Estonia in 2007 was followed up and compared with a matched full‐term (FT) control group. A logistic regression model was used to test associations between risk factors and adverse outcomes. Results: No impairment was found in 60% of the VLGA infants. Neurodevelopmental impairment was noted in 12% of VLGA infants, with 8% of the infants affected by cerebral palsy without independent walking, 5% with cognitive delay, 10% with language delay and 1% with hearing impairment. The differences between preterm and FT infants in terms of the mean Cognitive, Language, and Motor Composite Scores assessed using the Bayley‐III scales were in excess of 0.5 SD. Somatic growth delay was a significant problem among preterm infants. The existence of severe neonatal cerebral lesions was the most significant predictor of adverse outcomes. Conclusion: In all domains studied, adverse conditions were more prevalent among VLGA infants than among the FT control group. Efforts to reduce neonatal morbidity in preterm infants should be a key priority for health care in Estonia. Abstract :